2009
DOI: 10.1159/000234321
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Trypsin Inhibitors Afford Cardioprotective Effects through Activation of PI3K-Akt and ERK Signal Transduction and Inhibition of p38 MAPK and JNK

Abstract: Background: We determined the effect of urinary trypsin inhibitors (UTI) in regional myocardial ischemia/reperfusion (I/R) injury and its underlying mechanisms involving the role of prosurvival kinases such as phosphatidylinositol-3-OH kinases (PI3K)-Akt and extracellular signal-regulated kinases (ERK 1/2) and apoptotic kinases such as p38 and JNK. Methods: The rats were anesthetized and subjected to an I/R insult consisting of 30-min left anterior descending coronary artery (LAD) occlusion followed by reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Therefore we hypothesize that AST may produce a marked effect through growth factors and downstream signaling pathways. The ERK, JNK and Akt signaling pathways may regulate neuronal survival and apoptosis following ischemia, but the majority of studies agree that the levels of p-ERK, p-JNK and p-Akt decrease after 24 h or more following ischemia (14,15), therefore the level of p-ERK, p-JNK and p-Akt was detected 22 h after reperfusion in the present study. The p-ERK levels were enhanced following use of a variety of protective agents, such as BDNF and erythropoietin (16)(17)(18).…”
Section: Discussionmentioning
confidence: 44%
“…Therefore we hypothesize that AST may produce a marked effect through growth factors and downstream signaling pathways. The ERK, JNK and Akt signaling pathways may regulate neuronal survival and apoptosis following ischemia, but the majority of studies agree that the levels of p-ERK, p-JNK and p-Akt decrease after 24 h or more following ischemia (14,15), therefore the level of p-ERK, p-JNK and p-Akt was detected 22 h after reperfusion in the present study. The p-ERK levels were enhanced following use of a variety of protective agents, such as BDNF and erythropoietin (16)(17)(18).…”
Section: Discussionmentioning
confidence: 44%
“…PI3K and cyclinD1 are crucial proteins in PI3K/ Akt signal pathway regulating cell proliferation and cell cycle (Rusyn et al, 2000;Wang et al, 2001;Kim et al, 2009). JNK known as a stress-activated protein kinase involved in JNK/MAPK signal pathway play important role in regulating cell proliferation (Wang et al, 2001).…”
Section: Klf4 and Curcumin Surpress Bgc-823 Cell Proliferation By Regmentioning
confidence: 99%
“…As an endogenous protection mechanism, the UTIs can counteract stress and attenuate the effects of stress-related injury. Kim et al (2009) found that the UTI has strong enzyme inhibitory activity, which inactivate multiple enzymes, including leukocyte elastase, hyaluronidase, thiol-enzyme, fibrinolytic enzymes, and the serine protease-like trypsin, α-chymotrypsin. The UTI has antiinflammatory effects and can directly affect the neutrophils and mononuclear macrophages; inhibit neutrophil infiltration; and the release of elastase, inflammatory mediators and mononuclear macrophage inflammatory cytokines like TNF-α, IL-1, and IL-8 (Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%